Hardening of leading edges of turbine blades by electrospark alloying - Kalinina, N.E.; Hlushkova, D.B.; Hrinchenko, O.D.; Kalinin, V.T.; Voronkov, A.I.; Kostina, L.L.; Nikitchenko, I.N.; Nosova, T.V.; Reznikov, A.A. (Вопросы атомной науки и техники, 2019)
With a purpose of creating anti-erosion protection on turbine rotor blades the experiments in electrospark alloying using electrodes made of different materials: Т15К6 hard alloy and 15Х11МФШ steel were conducted. Reduction of the roughness of a surface layer having a uniform thickness was achieved upon its hardening with a steel electrode. The electrospark alloying process was perfected. Tests of mechanical properties of blade samples hardened with steel revealed overmatch of GOST requirements for strength and ductility. Increasing of surface layer microhardness was also achieved. For anti-erosion protection of leading edges of the turbine rotor blades it is recommended to replace the applied electrode made of Т15 К6 alloy with the one made of 15Х11МФШ steel. Для формування протиерозійного захисту робочих лопаток турбіни проведені експерименти з електроіскрового легування електродами з різних матеріалів: твердого сплаву Т15К6 і сталі 15Х11МФШ. Досягнуто зменшення шорсткості поверхневого шару, отриманого легуванням сталевим электродом, при однаковій товщині поверхневого шару. Відпрацьовано режим електроіскрового легування. Випробування механічних властивостей зразків лопаток, зміцнених сталлю, показали перевищення вимог ДСТУ з характеристик міцності та пластичності. Досягнуто також підвищення мікротвердості поверхневого шару. Рекомендована заміна електрода із сплаву Т15К6, що використовується, на електрод із сталі 15Х11МФШ, для захисту від ерозії вхідних кромок робочих лопаток турбін. Для формирования противно эрозионной защиты рабочих лопаток турбины проведены эксперименты по электроискровому легированию электродами из различных материалов: твердого сплава Т15К6 и стали 15Х11МФШ. Достигнуто уменьшение шероховатости поверхностного слоя при одинаковой его толщине после упрочнения стальным электродом. Отработан режим электроискрового легирования. Испытания механических свойств образцов лопаток, упрочненных сталью, показали превышение требований ГОСТ по прочности и пластичности. Достигнуто также повышение микротвердости поверхностного слоя. Рекомендована замена применяемого электрода из сплава Т15 К6 на электрод из стали 15Х11МФШ для защиты от эрозии входных кромок рабочих лопаток турбин.